Pengaruh Penebaran Rumpon Sawit Tehadap Hasil Tangkapan Ikan Pancing Ulur Di Dusun Tuing Kabupaten Bangka - Akbari Ridhoni; Eva Utami; Kurniawan Kurniawan (Akuatik: Jurnal Sumberdaya Perairan, 2018)
One of the simple fishing gear that is used by fisherman of Tuing is fishing gear or hand line fishing. The purpose of this study is to analyze the influence and effectiveness of oil palm rumpon on the catch fish in the fishing area of Tuing, Bangka Regency. The results of research of oil palm rumpon to the catching fishing catches states there is a significant influence on the catch fish. The catch of fishing line during research was 7 species of fish, there are Ephinephelus timorensis, Lutjanus madras, Lutjanus erytropterus, Nemipterus furcosus, Nemipterus bipunctatus, Lutjanus russeli, Arius thalassinus. The number of fish caught at the point using the rumpon as much as 28.58 kg while at the point of not using rumpon as much as 6.37 kg